Good tax governance's role in the process of renewing economies - Brodzka, Alicja (Rola dobrych rządów w dziedzinie opodatkowania w procesie odnowy gospodarek, 2012)
The aim of the paper is presenting the most relevant issues of good tax governance matters. Soft-law initiatives, successfully implemented and refined, can improve states’ fiscal management. It also can – through enhanced international cooperation in tax matters – increase international financial security and transparency. As implementing common tax standards can enhance the wide positive effects in the process of renewing economies, good tax governance has become the subject of interests of both individual states and international organisations
Nauki o Finansach = Financial Sciences, 2012, Nr 1 (10), s. 21-31
Keywords: good tax governance; fair tax competition; international tax optimisation; international tax policy; dobre rządy w dziedzinie opodatkowania; uczciwa konkurencja podatkowa; międzynarodowa polityka podatkowa